2010
DOI: 10.1104/pp.110.168252
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Meristem Activity and Sprout Growth in Potato Tubers Require Both Cytokinin and Gibberellin      

Abstract: Reactivation of dormant meristems is of central importance for plant fitness and survival. Due to their large meristem size, potato (Solanum tuberosum) tubers serve as a model system to study the underlying molecular processes. The phytohormones cytokinins (CK) and gibberellins (GA) play important roles in releasing potato tuber dormancy and promoting sprouting, but their mode of action in these processes is still obscure. Here, we established an in vitro assay using excised tuber buds to study the dormancy-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
169
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(197 citation statements)
references
References 88 publications
12
169
0
2
Order By: Relevance
“…Since the mid-1950s, it has been known that application of GA triggers tuber sprouting (Brian et al 1955;Rappaport 1956;Rappaport et al 1957). The dormancy-releasing capacity of GA was confirmed more recently by either injecting GA below the apical bud complex or by bathing isolated tuber buds in GA 3 solution (Suttle 2004b;Hartmann et al 2011;Rentzsch et al 2012). In all these studies, treatment with bioactive GA species was able to terminate dormancy and to stimulate bud outgrowth.…”
Section: Hormonal Controlmentioning
confidence: 73%
See 2 more Smart Citations
“…Since the mid-1950s, it has been known that application of GA triggers tuber sprouting (Brian et al 1955;Rappaport 1956;Rappaport et al 1957). The dormancy-releasing capacity of GA was confirmed more recently by either injecting GA below the apical bud complex or by bathing isolated tuber buds in GA 3 solution (Suttle 2004b;Hartmann et al 2011;Rentzsch et al 2012). In all these studies, treatment with bioactive GA species was able to terminate dormancy and to stimulate bud outgrowth.…”
Section: Hormonal Controlmentioning
confidence: 73%
“…therein). Nonetheless, comparison of sprouting and non-sprouting tubers suggested that ethylene-associated signals may negatively influence sprout outgrowth (Hartmann et al 2011) (see Fig. 3).…”
Section: Hormonal Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…La papa (Solanum tuberosum L.) ha sido considerada como uno de los principales cultivos agrícolas a nivel mundial en cuanto a superficie, ubicada detrás de los cereales y algunos cultivos destinados a la agroindustria, como la soya y la caña de azúcar y conjuntamente con el maíz, el trigo y el arroz, representan los cuatro rubros alimenticios básicos de la seguridad y soberanía alimentaria en variadas formas de consumo por los diferentes segmentos del mercado, ocupa un lugar importante en la agricultura, economía y seguridad alimentaria, situándose en el tercer cultivo de mayor consumo en el mundo (Hartmann et al 2011). Esta especie para su cultivo se propaga clonalmente, es mayoritariamente autotetraploide, altamente heterocigota y sufre depresión aguda por endogamia (The Potato Genome Sequencing Consortium -PGSC.…”
Section: Introductionunclassified
“…However, the buds that are initiated when the shoot apical meristem (SAM) of their mother has transitioned into the reproductive state ('A and B' buds in tulip), are able to skip this kind of dormancy (Chapter 4 and (Rees 1968)). This particular dormancy is known as paradormancy and imposed by apical dominance (Lang et al 1987 (Yao and Finlayson 2015;González-Grandío et al 2017;GomezRoldan et al 2008;Liang et al 2010;Pasare et al 2013;González-Grandío and Cubas 2014;Wu et al 2015;Hartmann et al 2011). …”
Section: What Can We Learn From Axillary Bud Outgrowth In Tulip?mentioning
confidence: 99%